Management Information Systems Towards Improving the Quality of Nursing Care Services: A Literature Review - Neli Suharti; Tutik Sri Hariyati (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: Many developing countries are striving to further develop health information technology at the healthcare service level, particularly through the implementation of electronic health records (EHR). Objectives: This research aims to evaluate the quality and impact of implementing electronic health records in healthcare services from various perspectives. Methods: The research design employed in this study is a literature review, involving the collection of articles from selected databases, including PubMed and Cochrane. The article search started from the year 2014, and the Boolean operators used were "Electronic Health Record" OR "Electronic Medical Record" OR "EHR" AND "Quality" OR "Documentation" OR "Quality Documentation" OR "Quality Care" AND "Nurs*". The research design incorporated into this study is observational. Results: The use of Electronic Health Records (EHR) has a significantly positive impact on various healthcare service sectors. Hospitals that have fully implemented EHR show a significant improvement in the quality of patient medical records, a decrease in information delivery delays, and a reduction in patient admission costs. Conclusion: Investment in EHR technology can be considered a crucial step in enhancing the quality and efficiency of healthcare services while reducing operational costs. However, it is important to note that EHR implementation is not a straightforward task and requires consideration of various factors mentioned above to achieve optimal results in health information management.